PERSONALITY ADJUSTMENT OF SECONDARY SCHOOL TEACHERS - Kumar, M.Pavan; Baskaran, D. (International Journal of Psychosocial Rehabilitation, 2020)
Effective teachers need to be able to work in a constantly evolving environment and adjust their teaching methods based on the age of their students, the resources available and changing curriculum, practices and requirements. The present study was carried out to find out the level of personality adjustment of secondary school teachers. 525 teachers working at secondary level working in high and higher secondary schools of Kancheepuram district were taken as sample. The tool used for the present study was Personality Adjustment Inventory by Pavankumar and Dr. Baskaran (2019). It was found out that the level of Personality Adjustment of teachers at Secondary level in different dimensions was moderate, there is no significant difference in Personality Adjustment of teachers at secondary level with respect to qualification and there is significant difference in Personality Adjustment of teachers at secondary level with respect to experience.